Heat Stress Modulates a Placental Immune Response Associated With Alterations in the Development of the Fetal Intestine and Its Innate Immune System in Late Pregnant Mouse - Guo, Huiduo; Liu, Riliang; He, Jianwen; Yao, Wen; Zheng, Weijiang (Frontiers in Physiology, 2022)
The placenta is critical for the regulation of fetal innate immune function. Maternal heat stress (HS) impairs the immune function and the intestinal barrier in the offspring. However, the effects of maternal HS on the placental immune response, and the development of the fetal intestine and its innate immune system remain unclear. Fetal mice were divided into the utero control (IUTN) and heat stress (IUHS) groups according to the maternal ambient temperature. Transcriptome analysis revealed that the expressions of placental immune response-related genes such as macrophage antigen CD68, Fc gamma receptor 1 and 3 (fcgγ1 and fcgγ3) were increased, but the mRNA expression and protein levels of colony stimulating factor-1 (Csf1) were decreased in the HS group compared with the TN group (P < 0.05). Furthermore, there was no significant difference in the intestinal length normalized to pup weight between the IUTN and IUHS groups. The expression of genes (such as alpi and ttr) involved in fetal duodenum and jejunum development were down regulated by maternal HS, whereas the expression of genes enriched in the cell cycle were increased. The mRNA expression and protein levels of cell division cycle 6 (Cdc6) in the fetal duodenum and jejunum were much higher in the IUHS group than in the IUTN group (P < 0.05). Maternal HS also down-regulated the expression of genes enriched in the innate immune system in the fetal duodenum and jejunum. The mRNA expression and protein levels of interleukin 1 alpha (IL1a) were reduced in the IUHS group compared with the IUTN group (P < 0.05). Taken together, these data demonstrated that maternal HS modulated expression of genes in the placenta related to the immune response, and inhibited the development of the fetal intestine and its innate immune system.